THE INFLUENCE OF HUMAN RESOURCE PRACTICE AND CREATIVITY ON SMALL BUSINESS PERFORMANCE IN MEDAN JOHOR DISTRICT - Angga Ardi Prasetya Siregar; Rindang Ni Bulan; Winda Ardiani (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to determine the effect of Human Resource Practice and Creativity on MSME Business Performance in Medan Johor District. This type of research is quantitative research which is associative in nature. The population used in this study were MSME owners in Medan Johor District. Sampling was done non-randomly using judgment sampling technique. The number of respondents used as samples was 100 MSME units in Medan Johor District. The method of analysis of this research is statistical analysis using SPSS Version 25 software. Research Results There is a positive and significant influence of Human Resource Practice on MSME Business Performance in Medan Johor District. There is a positive and significant influence of Creativity on the Performance of MSMEs in Medan Johor District. There is a positive and significant influence of Human Resource Practice and Creativity on the Business Performance of MSMEs in Medan Johor District. From the results of the research conducted, it is obtained that Human Resource Practice is the dominant variable affecting MSME Business Performance in Medan Johor District by 65.8%, while the Creativity variable is the dominant variable affecting MSME Business Performance in Medan Johor District by 40.2%.